Jovanović, Željko (2020) Twentieth-Century Sephardic Authors form the Former Yugoslavia. A Judeo-Spanish Tradition. Studies in Hispanic and Lusophone Cultures, 41. Cambridge: Legenda-Modern Humanities Research Association, 208 pp. - Díaz-Mas, Paloma (Miscelánea de Estudios Árabes y Hebraicos. Sección Hebreo, 2021)
Jovanović, Željko (2020) Twentieth-Century Sephardic Authors form the Former Yugoslavia. A Judeo-Spanish Tradition. Studies in Hispanic and Lusophone Cultures, 41. Cambridge: Legenda-Modern Humanities Research Association, 208 pp. ISBN 978-1-78188-851-3